THE ASSESSMENT OF HEALTH PROTOCOL IMPLEMENTATION IN FOOD AND BEVERAGES BUSINESS DURING COVID-19 PANDEMIC ERA - Lusi Sandra Hutahaean; Muhammad Ilyas; Marsen Isbayuputra; Ray Wagiu Basrowi; Dewi Soemarko (The Indonesian Journal of Public Health, 2021)
ABSTRACT